PENGARUH RESPON MASYARAKAT TERHADAP PENGEMBANGAN TEMPAT WISATA ALAM PUNCAK GUNUNG GAJAH PANDANREJO (Prospect : Jurnal Manajemen dan Akuntansi, 2021)
The objectives to be achieved in this study are as follows To determine the effect of community response on the development of tourist attractions, Peak of Mount Gajah Pandanrejo. Data collection techniques through observation, interviews, questionnaires, documentation, and literature study. Sources of data using a questionnaire. The population in this study is the surrounding community who visit the tourist attraction. The sample used is 50 respondents. Data analysis techniques include Likert scale, validity test, reliability test, simple correlation coefficient, simple linear regression analysis, coefficient of determination, and T test. Based on the results and discussion in the previous chapter, it can be concluded that 1) Pearson Correlation value is 0.785, in the sufficient category (0.600 to 0.799). So it can be concluded that there is a relationship between the community's response to the development of Mount Gajah Pandanrejo tourist attractions, this means that if the community's response is good, tourism development will also increase; 2) The constant value is 4.782, meaning that if the product quality is zero, then customer satisfaction is 4.782, with a value of b = 0.667, meaning that if the public response increases by one point, the development of tourist attractions will also increase by 0.667; 3) The R2 value is 0.617, meaning that the community's response contributes 61.7% to the development of tourist attractions, and the remaining 39.3% is influenced by other factors not examined in this study, such as promotions, discounts, and so on; 4) the results of the t-test indicate the t-value of product quality is 8.785. While the ttable with a sample of 50 people, with a level of significance = 0.05 and a confidence level of 95%, the ttable value is 1.1711. So the value of tcount is greater than ttable (8.785 > 1.7711) or a sig value of 0.000 (< 0.05).